Punish no clone - R. L. Kochnev (Омский научный вестник: Серия "Общество. История. Современность")
This article is a commentary and supplementary study to the Russian translation of Mark Walker’s article «Branching Is Not a Bug; It’s a Feature: Personal Identity and Legal (and Moral) Responsibility» published in this journal. The article discusses the difficulties that type/token theory encounters when analyzing cases of the existence of art objects and persons over time. An alternative solution, based on the ideas of Derek Parfit, is proposed.